Searching for Cutaneous Leishmaniasis in Tribals from Kerala, India - S M, Simi (Medknow Publications, 2010)
BACKGROUND: In India, indigenous cases of cutaneous leishmaniasis (CL) are mainly confined to the northwestern region. But now, more and more case reports are coming in from other parts of India. In January 2009, a 26-year-old lady residing in a forest area in Thiruvananthapuram district of Kerala State presented with bluish red nodules on her upper extremities, of six months duration, which was clinically more in favor of cutaneous leishmaniasis. She had never gone out of the district of Thiruvananthapuram in her life. AIM: To investigate whether the patient hails from a new endemic focus of cutaneous leishmaniasis. SETTING AND DESIGN: An epidemiological investigation in the form of a survey was carried out in March 2009 by a multidisciplinary team among 63 persons residing in the Mele Aamala and Aayiramkala forest tribal settlements in Kuttichal Panchayat of Thiruvananthapuram district. MATERIAL AND METHODS: History taking and clinical examination of 38 persons in the area with special consideration to skin lesions was undertaken. Microbiological and histopathological examination of the skin lesions was done. Breeding places of sand fly and possible reservoirs of Leishmania were also simultaneously investigated. STATISTICAL ANALYSIS USED: The data obtained was tabulated as frequency and percentage. Chi-square test was done to find out the statistical significance of differences in distributions. RESULTS: Out of the 38 persons examined, active lesions were found in 12 persons and six had healed lesions. Tissue samples were obtained from seven out of the 12 suspected cases. Four of them showed Leishman Donovan (LD) bodies in tissue smears. Out of the cultures taken from three patients, one showed promastigote forms in Novy McNeal Nicolle (NNN) medium. Histopathological study was done in five patients and two patients had LD bodies, one had epithelioid cell granuloma and the other two had mixed infiltrate with predominantly macrophages. All the three investigations were carried out in three patients and out of them one showed positivity in all the three investigations and the rest two were positive in tissue smear and histopathological examination. Sandflies collected from the area gave an indirect evidence of its role in the disease transmission in the area. CONCLUSION: The clinical, microbiological and histopathological evaluation of the skin lesions was consistent with cutaneous leishmaniasis. But none of the patients gave history of travel outside the district before the onset of the disease and no one had newly moved into this area within the last two years. So this may be considered as probably a new focus of cutaneous leishmaniasis